Systematic Literature Review (SLR): Analisis Rekonsiliasi Fiskal Atas Laporan Keuangan Komersial Terhadap PPH Badan yang Terutang pada Perusahaan - Tiar Lina Situngkir; Salma Nurhasanah; Rahma Dini Aulia; Najwa Khoerunnisa; Rizka Dwi Syaharani; Sinta Apriyani; Nurul Aulia; Desi Jaelani; Dessy Herdiana; Muhammad Daffa Jauza Fikri (Masyarakat Ekonomi Syariah Bogor, 2024)
The aim of this research is to analyze fiscal reconciliation of commercial financial reports against corporate income tax that businesses must pay, as determined by the systematic literature review (SLR) approach. determining the amount of income tax due following fiscal adjustments and determining whether the recorded income or costs match the relevant tax measures. In order to explain this issue, this research gathers, evaluates, and synthesizes pertinent prior work from a variety of approved journals, including Sprott, Google Scholar, and Pop. Systematic Literature Review (SLR) is the research methodology employed in this study. Fifteen reviews of the literature address the research subject for 2019 and 2024. According to the study's findings, every organization prepares fiscal reconciliation and commercial financial reports with the same inconsistencies. Thus, there are disparities in the calculation of corporation tax payable as well.